Mechanical and vasomotor properties of piglet isolated middle cerebral artery. Issue 1 (18th December 2016) - Eriksen, Vibeke R.; Abdolalizadeh, Bahareh; Trautner, Simon; Greisen, Gorm; Sheykhzade, Majid
Abstract: Piglets are often used as experimental models for studying cerebrovascular responses in newborn infants. However, the mechanical characteristics of piglets' middle cerebral arteries (MCA) are not well characterized. Additionally, the vessels' response to dopamine, the most commonly used vasopressor in newborns, is not characterized in piglets' MCA. Finally, the influence of preterm birth on the dopamine response is not known. The aim of this current was to compare by wire myography the active and passive mechanical characteristics and dopamine concentration–response relations of MCAs isolated from preterm and term newborn piglets. Second‐order branches of the MCA with a diameter <400  μ m were chosen for study. The active and passive mechanical properties were comparable between vessels from six preterm (90% gestation, nsegments   = 11) and nine term (nsegments  = 22) newborn piglets. The response to increasing concentrations of dopamine was biphasic, starting with vasodilation in the 1 nmol/L–0.3   μ mol/L concentration range followed by vasoconstriction at higher concentrations. The response was very similar between the two groups. In conclusion, the mechanical properties of the MCA as well as the response to dopamine were comparable between term and 90% gestation preterm piglets.